PENGARUH PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS TERHADAP STRUKTUR MODAL: (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Nurbayani Nurbayani; Jamilah Jamilah; Habib Muhammad Shahib; Teri Teri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to determine the effect of company growth (Asset Growth) and profitability (ROA) either partially or simultaneously on the capital structure (DER) of the Consumer Goods Industry companies listed on the Indonesia Stock Exchange. The independent variable in this study is Company Growth (X1) and Profitability (X2), while the dependent variable is Capital Structure (Y). This type of research is a causal research and the data used is secondary data obtained from documentation techniques. This study examines consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used was purposive sampling. The analytical method used is multiple linear regression analysis. The results of this study indicate that partially company growth (Asset Growth) has a positive and significant effect on capital structure (DER), and profitability (ROA) has a negative and significant effect on capital structure (DER). Meanwhile, simultaneously company growth (Asset Growth) and profitability (ROA) have a positive and significant effect on capital structure (DER).